Identification of p.His119Leu mutation in the G6PC gene of a Vietnamese patient with glycogen storage disease type Ia - Hoang, Nguyen Huy; Dung, Vu Chi; Tung, Nguyen Van; Lan, Nguyen Ngoc; Dung, Ha Thi (Academia Journal of Biology, 2020)
Glycogen storage disease type Ia (GSD Ia), a rare autosomal inherited disorder, is characterized by accumulation of excessive glycogen and fat in the liver. Primary symptoms of GSD Ia include hypoglycemia; metabolic acidosis; elevated levels of lactate, uric acid and lipids; hepatomagaly and growth retardation. Glycogen storage disease type Ia was caused by mutations in the G6PC gene. In this study, mutations in a Vietnamese patient with glycogen storage disease type Ia were analyzed using the whole exome sequencing method. A missense mutation c.356A>T (p.His119Leu) in the G6PC gene of the patient was identified in exon 3. Genetic analysis confirmed that this mutation was present under homozygous form In-silico analyses using SIFT and Mutation Taster confirmed the damaging effects of this mutations on the function of the proteins. This result enriches knowledge of the G6PC gene mutation spectrum and provides genetic data for further studies on glycogen storage disease type Ia in Viet Nam.